COMMUNICATIVE DISCOURSE AND COMMUNICATIVE STRATEGY - Razakova , Nargiza Xursanboevna (Educational Research in Universal Sciences, 2024)
This article describes the political discourse and its specific features, associated types of analysis. Participants of political discourse and their deliminatin during the communication were also studied.